2008
DOI: 10.3821/1913-701x(2008)141[278:ioapac]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pharmacist-managed anticoagulation clinic on clinical events

Abstract: BackgroundAnticoagulation management services (AMSs) are widely used for anticoagulation management in many countries. Our AMS is a pharmacist-run ambulatory clinic with a physician advisory committee that manages patients referred with complicated anticoagulation histories. This paper assesses the adequacy of anticoagulation, rates of anticoagulant-related events and associated health care resource utilization for patients before and after referral to our AMS.MethodsConsecutive patients referred to the AMS wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
89
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 14 publications
(13 reference statements)
5
89
0
Order By: Relevance
“…45,48 In contrast, the results of many low-quality observational studies have reported higher TTR and better outcomes in patients when anticoagulant therapy is managed by an AMS compared with usual care. [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] The absolute difference in TTR between AMS and pletion. 67 THINRS was more promising in that ‫ف‬ 80% were able to pass a PST competency assessment, but 16% switched from PST to the clinic testing group during the study.…”
Section: Anticoagulation Management Services For Vkasmentioning
confidence: 99%
“…45,48 In contrast, the results of many low-quality observational studies have reported higher TTR and better outcomes in patients when anticoagulant therapy is managed by an AMS compared with usual care. [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] The absolute difference in TTR between AMS and pletion. 67 THINRS was more promising in that ‫ف‬ 80% were able to pass a PST competency assessment, but 16% switched from PST to the clinic testing group during the study.…”
Section: Anticoagulation Management Services For Vkasmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] There is evidence that clinical outcomes in patients receiving care within pharmacist-managed programs are either comparable 14,20 or superior 18,19 to those achieved in physician-managed programs. The increasing use of OPAT as a cost-saving measure provides a prime opportunity for pharmacists to become involved in this form of care.…”
mentioning
confidence: 99%
“…7 In contrast, warfarin's anticoagulation is due to its indirect effects on the clotting cascade, taking several days to inhibit hepatic synthesis of vitamin K-dependent clotting factors. 5 Its full anticoagulant effects are not realized until circulating clotting factors are eliminated.…”
mentioning
confidence: 99%
“…3,4 However, maintaining warfarin therapy within its narrow therapeutic window is challenging, even for specialized anticoagulation clinics. 5 Many factors contribute to the variable dose response of warfarin, such as inter-individual variability, comorbidities and drug and food interactions. 5 Dabigatran is a novel therapeutic alternative that provides more predictable anticoagulation with less laboratory monitoring, and it is poised to take over some of warfarin's role in AF stroke prophylaxis.…”
mentioning
confidence: 99%
See 1 more Smart Citation